Investigation and analysis of crime cases in Subang Jaya district by using : geographic information system [GIS] approach / Ameliya Bhandal Shah Narinder - Shah Narinder, Ameliya Bhandal (2018)
Land use planning plays a crucial role in creating a balance between the needs of society, physical development and the ecosystem. However, most often poor planning and displacement of land uses particularly in urban areas contribute to social ills such as criminal activities. This research explains the spatial relationship of criminal activities on urbanization planning and their implications on the society at large. Spatial statistics was used to show patterns, trends and spatial relationships of crimes and land use planning. Data on crime incidents were obtained from the Royal Malaysia Police Department.